Complexo CLIMAAT-TERCEIRA-NARE para a monitorização da composição da atmosfera na camada limite do Atlântico Norte - Fialho, Paulo; Henriques, Diamantino; Carvalho, Fernanda; Barata, Filipe; Azevedo, Eduardo B. (2005)
Comunicação apresentada no 4º Simpósio de Meteorologia e Geofísica da APMG – 6º Encontro Luso-Espanhol de Meteorologia, Sesimbra, 14-17 Fevereiro de 2005. As a result of the partnership between the University of Azores, and the Association for the Study of the Insular Environment through the Environment Observatory and the Meteorological Institute, during the 2004 summer it took place the beginning of the installation of the CLIMAAT – TERCEIRA – NARE (INTERREG IIIB – Projecto CLIMAAT – MAC 2.3/A3) platform. In this stage, it was also installed in the José Agostinho observatory, near the city of Angra do Heroísmo, several equipments to monitoring the atmospheric and sun irradiation. Near the coast, at the moment, and beside the meteorological common parameters, pressure, temperature, relative humidity, precipitation, wind direction and intensity some measurements of the black carbon and iron oxide aerosol absorption coefficients were also done. The results of this project should contribute to the study of the evolution and composition of the North Atlantic atmosphere, and in that matter to the study of the Global Changes, namely as a land platform of reference to remote sensing satellite systems. This platform is part of the Azores Global Atmosphere Monitoring Complex (AGAMC).